Implementation of an Information System for Classroom Reservation at Esa Unggul University - Siti Rodiyah; Samuel Mahesa Sinulingga; Farrel Reyhan Putra; Muhammad Fathi Aryasatya; Ardo Kusdaryanto; Rovy Sulistiyono; Bambang Irawan (Universitas Islam Kuantan Singingi, 2025)
The manual management of room reservations at Esa Unggul University has long faced various administrative challenges, including irregular scheduling, delays in the approval process, and limited access to real-time room availability information. These issues reduce the overall efficiency of academic and administrative services. To address these problems, this study aims to design and implement a web-based information system that facilitates a more structured, transparent, and efficient room reservation process.The system was developed using the CodeIgniter 4 framework for the backend, while Bootstrap 5 and custom CSS were utilized for the frontend interface. MySQL served as the database management system, and application security features were enhanced with session-based authentication, input validation, data encryption, CSRF protection, Honeypot, and CloudFlare integration. Testing was conducted using the gray box method to evaluate both code reliability and system functionality from the user’s perspective.The results indicate that the application effectively handles room reservation requests, minimizes scheduling conflicts, and supports administrative staff in centrally monitoring room usage. This research contributes significantly to the digital transformation of campus administration and may serve as a reference for developing similar systems in other higher education institutions.